1969
DOI: 10.1038/bjc.1969.62
|View full text |Cite
|
Sign up to set email alerts
|

The growth and cell population kinetics of spontaneous tumours in domestic animals.

Abstract: INVESTIGATIONS into the relationship between cell proliferation and overall tumour growth rate in human cancer have to contend with the major limitation that only rarely can both cell kinetic data and information on volume growth rate be obtained in one and the same patient. When a case is operable it is usually inadvisable to delay treatment in order to estimate growth rate; when, for instance in the case of lung secondaries, it is right to leave tumours untreated, tissue specimens are seldom available.It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…What is remarkable is the failure of tritiated thymidine to label cells in regions of a tumour that show mitotic activity. So far as we are aware, the only previous report of such an observation (also in canine tumours) is that of Owen and Steel (1969). The main difficulty in establishing the existence of such a phe;nomenon is that in an autoradiograph there are always some cells that have a low grain count and which might be scored as labelled if the autoradiographic exposure time were increased.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…What is remarkable is the failure of tritiated thymidine to label cells in regions of a tumour that show mitotic activity. So far as we are aware, the only previous report of such an observation (also in canine tumours) is that of Owen and Steel (1969). The main difficulty in establishing the existence of such a phe;nomenon is that in an autoradiograph there are always some cells that have a low grain count and which might be scored as labelled if the autoradiographic exposure time were increased.…”
Section: Discussionmentioning
confidence: 97%
“…There are good reasons for believing that in this tumour the growth limitation is caused by an immune reaction of the host against the TVT cells (Sticker, 1906;DeMonbreun and Goodpasture, 1934;Powers, 1968;Cohen, 1971 Growth limitation of the transmissible venereal tumour does not greatly influence the timing of the mitotic cycle of tumour cells. This is well established for G2 and S and there was no evidence for a lengthening of G1 or the whole cell cycle in the more slowly growing tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with transplantable rodent tumours (Hirst et al, 1982) have shown that tumour cells migrate from oxygenated to hypoxic regions at a rate of 1.1-2.2 jm h-as cells close to capillaries proliferate and hypoxic cells distant to capillaries are displaced into adjacent necrotic regions. While the mean potential doubling time for spontaneous canine tumours (5.4 ± 2.9 days; range 2.3-16 days) (Owen & Steel, 1969) is much greater than that for rodent tumours (1-2 days) and the cell migration rate in the spontaneous tumours might, therefore, be expected to be much lower, the possibility that previously well-oxygenated cells had migrated into the hypoxic regions by the end of the 24 h labelling period cannot be completely ruled out. The effect would be an apparent decrease in the hypoxic fraction because labelled hypoxic cells lost to necrosis would not have been counted in the morphometric analysis.…”
Section: Discussionmentioning
confidence: 94%
“…The widespread occurrence of labelled cells in the spontaneous tumours in the absence of necrosis might have been interpreted to mean that cell migration processes were not occurring. However, the overall cell loss factors for rodent and spontaneous canine tumours are similar (Hirst et al, 1982;Owen & Steel, 1969) so that mechanisms of cell loss other than cell migration into necrotic regions may exist.…”
Section: Discussionmentioning
confidence: 99%